2019
DOI: 10.1021/acs.jafc.9b04425
|View full text |Cite
|
Sign up to set email alerts
|

Nanocorona Formation between Foodborne Nanoparticles Extracted from Roast Squid and Human Serum Albumin

Abstract: Foodborne nanoparticles (FNPs) produced by roasting have attracted the attention of people, owing to their safety risk to body health. Herein, we reported the formation, physicochemical properties, elemental composition, biodistribution, and binding with human serum albumin (HSA) of FNPs extracted from roast squid. The results showed that the FNP size gradually decreased from 4.1 to 2.3 nm as the roasting temperature changed from 190 to 250 °C. The main component elements of FNPs are carbon, oxygen, and nitrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 44 publications
(96 reference statements)
1
16
0
Order By: Relevance
“…When the CDs cross the intestine wall and enter the bloodstream, they can form coronas with serum proteins after interaction. 16 It is well known that HSA is the most abundant protein in the serum. 22 In this study, the interaction between the CDs and HSA was studied to elucidate the formation of protein coronas in vitro.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the CDs cross the intestine wall and enter the bloodstream, they can form coronas with serum proteins after interaction. 16 It is well known that HSA is the most abundant protein in the serum. 22 In this study, the interaction between the CDs and HSA was studied to elucidate the formation of protein coronas in vitro.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…When humans consume roast beef, endogenous CDs are inevitably absorbed by the digestive system and have serious consequences in human health. As the CDs have small size, large specific surface area, and high surface free energy, they can absorb a variety of serum proteins through interaction with the functional groups to form protein coronas . Among the plasma proteins, HSA, accounting for about 60% of the total plasma protein, has important physiological functions including storage and transportation of endogenous metabolites as well as exogenous ions and small molecules. , The CDs may form protein coronas with HSA, resulting in changes in the CD properties.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the height of FCDs in roast duck was 2-4 nm, and as the roasting temperature increased from 200-300 C, the height of FCDs became more uniform [6]. The height of FCDs in grilled squid was 2-6 nm, and it was speculated that the height of FCDs was comparable with the size of TEM [19]. The FCDs with an ultra-small size and high surface to area ratio may have great potential interaction with human blood proteins.…”
Section: Characterization Of Fcdsmentioning
confidence: 94%
“…Turci et al found that the affinity and adsorption stability of SiO 2 nanoparticles with BSA, bovine lactoperoxidase, ribonuclease A and egg lysozyme were all dependent on surface charge distribution and isoelectric point of proteins (Turci et al, 2010). Second, the bridging effect, which generates from the increase in the strength of ions (such as calcium ions) in reaction system leading to the enhancement in binding force between HSA and nanoparticles, thus promoting the adsorption of HSA (Liu et al, 2019). Third, specific receptor-ligand interactions, may also cause strong electrostatic interaction, such as both BSA and HSA interacting electrostatically with citrate ligands on the surface of nanoparticles through lysine residues.…”
Section: Effect Of Electrostatic Interaction On the Formation Of Prot...mentioning
confidence: 99%
“…Yuan et al reported that the combination of nanoparticles and HSA was a complex process, reducing protein α-helix content and the extension of peptide chains (Yuan et al, 2018). The endogenous nanoparticles extracted from grilled squid (Liu et al, 2019) and duck (Cong et al, 2018) changed the secondary structure proportion of HSA. As the concentration of particles increased, the α-helix content of HSA gradually decreased (Figure 3a).…”
Section: F I G U R Ementioning
confidence: 99%